1992
DOI: 10.1164/ajrccm/146.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced Cough in Humans

Abstract: We have evaluated the properties of capsaicin as a selective cough-inducing agent in healthy human subjects. Despite frequent coughing, the subjects could inhale repeated breaths of capsaicin aerosol during 60 s without difficulty. Cough started immediately on inhalation and was most intense during the first 30 s. Cough always disappeared promptly when the capsaicin inhalation was terminated. The cough response was well reproducible and concentration-dependent up to 10 microM; at higher concentrations there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 4 publications
4
87
0
4
Order By: Relevance
“…The testing of cough sensitivity with capsaicin inhalation is otherwise often performed with a "single-breath" technique using increasing concentrations of capsaicin until the individual coughs, for example, two or five times (C2 or C5), which has shown a good reproducibility [41,42]. Others, who used both techniques, found that the tidal breathing method with a fixed time and concentration showed good reproducibility and dose-response relationship in the short term, as well as in the long term [8,43]. The single-breath technique was more dependent on a standardized inhalation technique compared to the fixed time and concentration technique [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testing of cough sensitivity with capsaicin inhalation is otherwise often performed with a "single-breath" technique using increasing concentrations of capsaicin until the individual coughs, for example, two or five times (C2 or C5), which has shown a good reproducibility [41,42]. Others, who used both techniques, found that the tidal breathing method with a fixed time and concentration showed good reproducibility and dose-response relationship in the short term, as well as in the long term [8,43]. The single-breath technique was more dependent on a standardized inhalation technique compared to the fixed time and concentration technique [44].…”
Section: Discussionmentioning
confidence: 99%
“…After capsaicin inhalation, changed levels of nerve growth factor in nasal secretions have been detected, indicating a neurochemical imbalance in the airways, which is related to SHR [6]. Cough sensitivity to capsaicin is a measure of airway sensory reactivity [7,8]. Patients with SHR react more strongly than healthy individuals to provocation with inhaled capsaicin, and the cutoff values for a positive reaction have been determined [4].…”
Section: Introductionmentioning
confidence: 99%
“…First, the phenomenon could be due to a steeper stimulus/response relationship for capsaicin than fog. Concentration-or dose-dependency of cough frequency has repeatedly been demonstrated for capsaicin (e.g., Midgren et al, 1992) but no data are available for fog. Since the present experiments were designed to investigate specifically the reflex respiratory responses evoked by threshold capsaicin and fog concentrations, they cannot provide information on the stimulus/response relationships for these tussigenic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of sensitivity and of dose-response curve for capsaicininduced coughs has been established in normal subjects [17]. In this study, the cough threshold to inhaled capsaicin was measured as an index representing airway cough sensitivity, which was defined as the lowest concentration of capsaicin eliciting five or more coughs [2,4,6].…”
Section: Discussionmentioning
confidence: 99%